MRI-Diagnostics of Injuries and Diseases of the Ankle Joint and Foot (Review of Literature) - Radchenko, K.A.; Gayko, O.G. (TERRA ORTHOPAEDICA, 2020)
Summary. Diseases and injuries of the ankle joint and foot make up 6-12% of the total number of injuries and diseases of the musculoskeletal system. The article is devoted to the main diagnostic possibilities of magnetic resonance imaging (MRI), determination of indications for examination and protocols for the study of the ankle joint and foot. Based on the analysis of literature data, the high diagnostic efficiency of MRI in the identified pathologies of bone and soft tissue structures of this segment of the lower extremity was determined.